2012
DOI: 10.5430/jha.v1n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Patient Accessible Electronic Health Records for the Chronically Ill: A Review of the Literature

Abstract: Background: Consumers with chronic conditions account for approximately 70% of all healthcare spending. The Chronic Care Model is a healthcare paradigm whose purpose is the achievement of improved patient outcomes by facilitating the delivery of patient-centered, evidence-based care. We conducted a review of the literature to examine the role patient accessible electronic health records (PAEHR) may play in implementing and supporting the Chronic Care Model. Methods:A review of the literature was conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(199 reference statements)
1
4
0
Order By: Relevance
“…Notable is that the portion of patients in our study that logged in to view their personal information is much larger than the portion that only viewed the general information on the patient web portal. Previous studies have also found that personal information, and especially laboratory results, are more useful than general information to patients with chronic conditions [13]. Concordantly, we can conclude that our portal with EMR access foresees in a need in these patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Notable is that the portion of patients in our study that logged in to view their personal information is much larger than the portion that only viewed the general information on the patient web portal. Previous studies have also found that personal information, and especially laboratory results, are more useful than general information to patients with chronic conditions [13]. Concordantly, we can conclude that our portal with EMR access foresees in a need in these patients.…”
Section: Discussionsupporting
confidence: 78%
“…Most patients reported using the login service prior to a consultation, which could indicate that they used it to prepare for the conversation with their doctor or nurse [ 34 , 38 ]. Two recent systematic reviews on the effects of patient web portals with EMR access show that only a few other studies have included empowerment-related outcomes into their evaluations, with small and inconclusive results [ 13 , 10 ]. Tuil et al [ 9 ], who conducted a study among patients undergoing IVF treatment, could not detect any enhancement in patient empowerment over time either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the patient's perspective, participants were very keen on having access to the Recipient Portal. Research has shown that having access to personalized information is more useful compared with having access to general information of patients with chronic conditions (e.g., Urowitz et al, 2012). In the current study, most participants found it very useful having personalized information (e.g., warranty information) at a single location, accessible at any time.…”
Section: Discussionmentioning
confidence: 52%
“…Systematic reviews on the effects of portals with EHR access [ 25 - 27 ] indicate that few studies have investigated outcomes concerning patient engagement or empowerment, with studies typically providing nonsignificant findings. Kruse et al [ 27 ] found only 27 studies of relevance to impact—those measuring meaningful outcomes such as patient participation in medical decisions, patient-provider communication, or satisfaction.…”
Section: Introductionmentioning
confidence: 99%